Analysis of the Use of Fake GPS Applications on Drivers of PT GoTo Gojek Tokopedia Tbk (GOTO) - Alhafidz, Muhammad Fikri; Hasibuan, Eka Hayana (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The purpose of this study was to determine the use and system used to detect the fake GPS application on PT Goto Gojek Tokopedia Tbk driver partners in the competition between Gojek drivers in Surabaya. The research method used is a qualitative method, which is obtained based on the results of field research (field research). The data required in this study were collected using observation, interview, and literature study techniques, which were then analysed using descriptive techniques in describing data about the use of the Fake GPS application on PT Goto Gojek Tokopedia Tbk partners. The results of this study conclude that the use of the Fake GPS application by PT Goto Gojek Tokopedia Tbk drivers is carried out without coercion, without fraud, and without oversight, but the driver violates company rules regarding the use of additional applications in the form of fake GPS. The system used to detect fake GPS applications in this research is based on ensemble learning using the AdaBoost and XGBoost algorithms. The learning ensemble is able to detect fake GPS applications very well.